Partisipasi Masyarakat dalam Pengelolaan Lingkungan Ekowisata di Mangrove Center Kabupaten Tuban - Mustika Rahmawati, Ditri Asma; Cintamulya, Imas (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2020)
Mangrove Center Tuban (MCT) Jenu is a conservation area of mangrove forests in Tuban District, it is located on the north coast with a width of about 56 ha. This MCT area has been developed into an ecotourism area with the object of mangrove forests and sea firs. The sustainability of MCT as an Ecotourism area depends on the role of the community and its participation in the management of the ecotourism. As the purpose of this research is: 1) to describe the community perception of environmental management in the MCT Jenu eco-tourism area; 2) to describe community participation in environmental management in the MCT Jenu eco-tourism area, and 3) to find out the affecting factors of community participation in environmental management in the MCT Jenu Tuban ecotourism area. This study was conducted from November 2019 to January 2020. The number of respondents were 20 people whose presence of Wana Bahari group; Wana Asri group, and the visitors of them. Data collection was done with field observation, dissemination, and interviews. The data obtained were analyzed descriptively quantitatively. The result showed that the level of community perception about the management of ecotourism in the MCT area and the level of community participation in the management of ecotourism in the MCT area was in a good category. While affecting factors of public participation in ecotourism management derived from the economic activity and the role of the MCT Foundation in the management of the MCT area. Research results are expected to benefit for: 1) raising public awareness of the importance of maintaining the mangrove forest conservation area through their participation in environmental management in the MCT eco-tourism area; 2 strengthening cooperation between communities, and MCT managers for the continuity of the MCT area who have a function for the conservation of mangrove forests.